Construction method for reinforced concrete frame structure / Syed Ahmad Najmi Shahabudin Syed Nasiruddin - Syed Nasiruddin, Syed Ahmad Najmi Shahabudin (Universiti Teknologi MARA, Perak, 2019)
Reinforced concrete framed structure is a very important thing to elaborate. It was the most common type of modern building internationally. As the name suggests, the type of building in site Kolej Vokasional Kulim consists of a frame structure. Horizontal members of this frame are called beams and slabs, and vertical members are called columns. including staircase. In this report will discuss about the construction method of those reinforced concrete framed structure which are column, beam, slab and staircase. Another objective of this report was to study the defects that occur and ways to handle the defects efficiently. The methods of data collection are unstructured interviews with no specific set of predetermined questions to site staff. although the interviewers usually have certain topics in mind that they wish to cover during the interview. Therefore, semi-structured interviews were also performed to even more people such as architect and the consultant. Including document reviews and observation that was carried out on site.